Predictors of High Hospital Costs among Patients with Chronic Illness who develop Acute Respiratory Failure (GP753) - Khandelwal, Nita; Downey, Lois; Engelberg, Ruth; Curtis, J. Randall; May, Peter (Journal of pain and symptom management, 2020)
Objectives Identify predictors of high hospital costs for patients with chronic illness who develop acute respiratory failure Recognize the complexity of identifying patients who may benefit most from targeted interventions to improve value-based care. Importance. Patients with acute respiratory failure and underlying chronic illness are at high risk for burdensome care. Objective(s). Our objective was to identify predictors of high-cost, potentially burdensome care among patients hospitalized with acute respiratory failure. Method(s). Data were derived from a multi-hospital system electronic health record linked to hospital financial records (2011-2017). Eligible patients were age $18 years with at least one of nine Dartmouth Atlas chronic conditions and received mechanical ventilation for >48 hours in the intensive care unit (ICU). Our primary outcome was total hospital costs for the hospitalization with the qualifying ICU admission, adjusted for inflation and analyzed using generalized linear models. Predictors were number and type of chronic conditions, and prior healthcare utilization. Results. Our sample included 4,892 patients. Mean age was 59 (SD: 15); 36% were female. Mean number of chronic conditions was 2.3 (SD 1. 38). Median ICU length of stay was 12 days (IQR: 7, 22); median inpatient length of stay was 20 days (IQR: 11, 33). Median Apache II score was 22 (IQR: 12, 28). Median hospital costs were $135k (IQR: 78k, 228k). Hospital mortality was 35%. For survivors and decedents, hospital costs in the prior year were associated with higher costs during the admission of interest (b¼0.0004, p<0.001) and dementia was associated with lower costs (survivors: b¼-23.8, p¼0.018; decedents: b¼- 45.7, p<0.001). Among decedents, number of diagnoses was positively correlated with costs (b¼24.0, p<0.001); among survivors, chronic renal failure was positively correlated (b¼37.4, p<0.001). Conclusion(s). Higher hospital costs in the year prior to a hospitalization with acute respiratory failure was predictive of higher costs during the current admission. Individual conditions and multi-morbidity predict costs, but had a differential effect depending on survival. Impact. Patients at risk for high-cost hospitalizations may allow targeted interventions to improve value-based care. Identification efforts must address a complex web of determinants including diagnosis, proximity to death, multi-morbidity burden and prior healthcare use.